2010
DOI: 10.1002/bjs.7161
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based management of pain after haemorrhoidectomy surgery

Abstract: Local anaesthetic infiltration, either as a sole technique or as an adjunct to general or regional anaesthesia, and combinations of analgesics (non-steroidal anti-inflammatory drugs, paracetamol and opiates) are recommended. If appropriate, a stapled operation may be preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 82 publications
0
75
1
4
Order By: Relevance
“…19 Additional examples where rA was neglected included open reconstruction of knee ligaments (rank, 15) and hemorrhoid resections with plastic reconstruction (rank, 23), which are both known to be painful procedures. Although randomized controlled trials (rCTs) have demonstrated clinically significant pain reduction after femoral nerve blocks 25 and wound infiltration with local anesthesia, 26 in our study population these techniques were hardly ever used.…”
Section: Discussionmentioning
confidence: 99%
“…19 Additional examples where rA was neglected included open reconstruction of knee ligaments (rank, 15) and hemorrhoid resections with plastic reconstruction (rank, 23), which are both known to be painful procedures. Although randomized controlled trials (rCTs) have demonstrated clinically significant pain reduction after femoral nerve blocks 25 and wound infiltration with local anesthesia, 26 in our study population these techniques were hardly ever used.…”
Section: Discussionmentioning
confidence: 99%
“…The grave problem about the conventional hemorrhoidectomies is the postoperative pain starting just after the operation and still exists as a major issue, even though the procedure is considered to be an old intervention. This aspect has been analyzed in several studies, as the hemorrhoidectomy is a procedure in which the severe pain necessitating opioid drugs in analgesic management occurs in 20-40% of patients [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The consensus is that the aetiology of haemorrhoids is multi-factorial and can be analysed from the point of view of the complex anal structure and function (Gan et al, 2010;Joshi and Neugebauer, 2010): The anus is the excretory outlet for faeces which are composed mainly of bacteria. It frequently sustains injuries such as rupture by hardened stool or abrasion by sanitary tissues.…”
Section: Discussionmentioning
confidence: 99%